2021
DOI: 10.1158/1078-0432.ccr-21-2225
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of the Efficacy and Safety of Oral Selinexor in Recurrent Glioblastoma

Abstract: Purpose: Selinexor is an oral selective inhibitor of exportin-1 (XPO1) with efficacy in various solid and hematologic tumors. We assessed intratumoral penetration, safety, and efficacy of selinexor monotherapy for recurrent glioblastoma. Patients and Methods: Seventy-six adults with Karnofsky Performance Status ≥ 60 were enrolled. Patients undergoing cytoreductive surgery received up to three selinexor doses (twice weekly) pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…To test this hypothesis, we obtained RNA-seq of tumor samples from 57 patients with recurrent glioblastoma who were treated with selinexor monotherapy as part of the phase II KING trial (NCT01986348). 12 Overall, we found that patients with higher expression of the signature experienced improved PFS, although statistical significance was not achieved (log rank P = 0.078, Cox PH P = 0.0734, HR = 0.549, Fig S3A). However, patients who achieved a clinical benefit with a partial response (PR) or better had significantly higher signature expression (Wilcoxon P = 0.0034, Fig S3B ).…”
Section: King Study In Recurrent Glioblastomamentioning
confidence: 79%
See 2 more Smart Citations
“…To test this hypothesis, we obtained RNA-seq of tumor samples from 57 patients with recurrent glioblastoma who were treated with selinexor monotherapy as part of the phase II KING trial (NCT01986348). 12 Overall, we found that patients with higher expression of the signature experienced improved PFS, although statistical significance was not achieved (log rank P = 0.078, Cox PH P = 0.0734, HR = 0.549, Fig S3A). However, patients who achieved a clinical benefit with a partial response (PR) or better had significantly higher signature expression (Wilcoxon P = 0.0034, Fig S3B ).…”
Section: King Study In Recurrent Glioblastomamentioning
confidence: 79%
“…Gene-level read counts were obtained from pretreatment tumors from 57 patients with recurrent glioblastoma that were enrolled in the phase 2 KING study. 12…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the importin XPO1 or CRM1 via selinexor has reduced proliferation and prolonged survival in GBM animal models [105]. A phase 2 study on efficacy, safety, and intratumoral pharmacokinetics of selinexor monotherapy in recurrent GBM (KING Trial) [124] concluded that there was a clinically relevant response in patients with GBM to a 80 mg weekly dose of selinexor in terms of prolonged progression-free survival [124]. The follow-up study NCT04421378 analyses the effect of selinexor in combination with standard of care therapy for newly diagnosed or recurrent GBM (https://clinicaltrials.gov/ct2/show/NCT04421378, accessed on 30 December 2021).…”
Section: Targeting the Cell Cycle Machinery In Gbmmentioning
confidence: 99%
“…We additionally used an unpublished dataset that was obtained as part of a collaboration with Massachusetts General Hospital (MGH). Overall, we identified and set aside 21 datasets 20,24,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] the evaluation setsas unseen data for evaluation. See Table S1 and Supplementary Note 1 for full details.…”
Section: Tuning and Evaluation Datasetsmentioning
confidence: 99%